CSR Spendings of Indonesia's IPO Prospectuses - Zuraida, Zuraida; Sugianto, Sugianto (Jurnal Keuangan dan Perbankan, 2021)
To raise large amounts of capital, companies usually conduct Initial Public Offerings (IPOs), which allows them to reach large numbers of potential investors. Prospectuses are used to inform the public of the nature and prospects of these offers. The prospectus contains financial and non-financial information such as Corporate Social Responsibility (CSR) spending. However, the level of disclosure is usually not uniform across companies. This study examines the nature and factors influencing CSR spendings disclosed by Indonesian companies in the prospectuses for the period 2012 - 2019. Research data was hand-collected and analyzed using descriptive statistics, Pearson correlations, and multiple regressions. The findings show that most companies disclose CSR efforts; fewer companies reveal the amount spent on CSR activities. Among companies disclosing CSR spending, more spending is allocated in the years leading to the IPO date (y) compared to previous years. Thus spending on y is relatively higher than y-1, follows by y-2 and y-3. CRS spending has a positive and significant relationship with company size. These findings are consistent across alternative model specifications. This study made an essential contribution to the CSR literature by providing Indonesia's first empirical evidence on the CSR expenditure in IPO prospectuses. DOI : https://doi.org/10.26905/jkdp.v25i2.5559